Iron Pyrite/Titanium Dioxide Photoanode for Extended Near Infrared Light Harvesting in a Photoelectrochemical Cell - Wang, Di-Yan (Sci Rep, 2016)
The design of active and stable semiconducting composites with enhanced photoresponse from visible light to near infrared (NIR) is a key to improve solar energy harvesting for photolysis of water in photoelectrochemical cell. In this study, we prepared earth abundant semiconducting composites consisting of iron pyrite and Titanium oxide as a photoanode (FeS(2)/TiO(2) photoanode) for photoelectrochemical applications. The detailed structure and atomic compositions of FeS(2)/TiO(2) photoanode was characterized by high-resolution transmission electron microscopy (HRTEM), energy-dispersive X-ray spectroscopy (EDS), powder X-ray diffraction (XRD), inductively coupled plasma with atomic emission spectroscopy (ICPAES) and Raman spectroscopy. Through the proper sulfurization treatment, the FeS(2)/TiO(2) photoanode exhibited high photoresponse from visible light extended to near infrared range (900 nm) as well as stable durability test for 4 hours. We found that the critical factors to enhance the photoresponse are on the elimination of surface defect of FeS(2) and on the enhancement of interface charge transfer between FeS(2) and TiO(2). Our overall results open a route for the design of sulfur-based binary compounds for photoelectrochemical applications.